Comparison of the Chronic Toxicity of Nickel to Temperate and Tropical Freshwater Species. (7th May 2019) - Peters, Adam; Merrington, Graham; Leverett, Dean; Wilson, Iain; Schlekat, Christian; Garman, Emily
Abstract: Reliable ecotoxicity data are required to derive thresholds protective for aquatic life that are scientifically defensible and practically implementable as environmental risk assessment and management tools. Much of the data that have been used to derive thresholds for environmental quality have been collected for temperate species. There are concerns that due to a lack of data for the different species present in tropical ecosystems, they may not be adequately protected by thresholds derived from temperate species. In the present study, chronic ecotoxicity data for nickel and freshwater species from different climatic regions have been collated. Comparisons were performed between tropical and temperate datasets on the basis of the threshold values and overall distributions of the ecotoxicity data, as well as between groups of species and closely related species from different climatic regions. The analysis indicated that the sensitivities of tropical and temperate species cover similar ranges. An approach based on the inclusion of as diverse a range of taxa as possible is recommended to ensure the protection of sensitive species in both temperate and tropical ecosystems. Environ Toxicol Chem 2019;38:1211–1220. © 2019 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.